Market Reactions to Dividend Increases and Cuts: A Decade-Long Event Study Analysis of the Warsaw Stock Exchange - Michałowski, Miłosz (Reakcje rynku na podwyżki i cięcia dywidend: Analiza zdarzeń na Giełdzie Papierów Wartościowych w Warszawie w ciągu ostatniej dekady, 2025)
Aim: This study examines how dividend increases and cuts influence stock prices on the Warsaw Stock Exchange over a decade, testing the signaling hypothesis and assessing market efficiency in an emerging market context. Methodology: Using an event study methodology, the author analysed 395 dividend increases and 232 decreases (2015-2024). Abnormal returns (AAR, CAAR) were calculated via the Market Model and Constant Mean Model, with statistical significance tested using one-tailed t-tests. Findings: Dividend increases triggered immediate positive reactions (+1.39% AAR on announcement day, p < 0.005), while cuts led to sharp declines (-1.23% AAR, p < 0.005). Cumulative effects were asymmetric: CAAR for decreases persisted at -2.97% (day +16), whereas post-announcement gains for increases partially reversed. Firms raising dividends exhibited higher yield (5.19%) and payout ratios (59.48%), signalling stability. Implications and recommendations: Practitioners should prioritise dividend policy as a strategic signal, particularly in emerging markets where reactions are amplified. Originality/value: This is the first decade-long event study on the WSE to compare dividend increases and cuts, offering insights into investor behaviour in Central and Eastern Europe. The dual-model approach strengthens reliability, while findings challenge assumptions about market efficiency in emerging economies.
Financial Sciences. Nauki o Finansach, 2025, vol. 30, no. 1, s. 35-45
Keywords: dividend policy; event study; Warsaw Stock Exchange; emerging markets; abnormal returns; polityka dywidendowa; badanie zdarzeniowe; Giełda Papierów Wartościowych; rynki wschodzące; nadzwyczajne stopy zwrotu